2019
DOI: 10.35449/jemasi.v15i1.37
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pertumbuhan Ekonomi Terhadap Disparitas Pembangunan Di Propinsi Sumatera Selatan

Abstract: Economic growth of any counties had positive and negative impact. A positive impact is an increase in national income and negatif impact are inequility of personal income distribution and development disparities. Economic growth in province of South Sumatera also had that impact. The purposes of this research is to prove empirically relationship and patterns of linkages between economic growth and development disparities. The data that used is secondary data obtained from Central Statistic Agency in the form o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Another measure of welfare level can also be seen from non-material as stated by (Hanemann, 1984) through education, health and nutrition levels, freedom to choose a job and guarantee a better future. Ningsih et al (2019) concluded that the results of the Williamson Index calculation show that the level of development inequality in the province of South Sumatra from 2010 -2017 and 2015-2017 is in the high category because the IW value is > 0.35. In 2014, the development inequality was very high because the IW value was close to 1, which was 0.90.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…Another measure of welfare level can also be seen from non-material as stated by (Hanemann, 1984) through education, health and nutrition levels, freedom to choose a job and guarantee a better future. Ningsih et al (2019) concluded that the results of the Williamson Index calculation show that the level of development inequality in the province of South Sumatra from 2010 -2017 and 2015-2017 is in the high category because the IW value is > 0.35. In 2014, the development inequality was very high because the IW value was close to 1, which was 0.90.…”
Section: Literature Reviewsmentioning
confidence: 99%